Assessment of Holarrhene Antidysenteric Phytochemical and Pharmacological Aspects (Wall.): Exploring the potential of Holarrhene antidysenterica for treating various diseases (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The efficacy, low cost and low side effects correlated with medications result in an ever growing amount of interest in medicinal plants. For the medicinal usage of their stemb bark, their leaves and their Ayurvedic seeds is prescribed for the wall of the Apocynaceae genus. Holarrhene antidysenterica(syn.H. pubescens). Studies of the phytochemical and pharmacological existence of the plant throughout the past century generated significant findings with respect to the present chemical components and also confirmed the herbs' historically asserted properties analgesic, anti-bacterial, anti-diarrhoeal, antiamoebic, anti-inflammatory and anti-hemorrhoidal activity. Furthermore, several other properties such as anti-malaria, anti-diabetic, anti-urolithic, antimutagenic, CNS, antigiotensin-conversion enzyme inhibitory activity and acetylcholinesterase have recently been discovered. This analysis addresses in greater depth the results of studies of the abovementioned properties of the plant and 68 alkaloids, which are derived from different plant components, to support their widely used treatment of a number of diseases and recommends potential study guidelines.